A comparison of the length and width of static inked two-dimensional bare footprints found on a hard compared to a soft surface. Issue 4 (July 2019) - Curran, Michael; Holmes, Isabelle
Abstract: In forensic intelligence-gathering it would be useful to evaluate if there are differences between static inked bare footprints captured on hard surfaces compared to soft surfaces. This was undertaken using samples from 30 undergraduate students. Initially a static footprint was taken for each participant on a hard surface and this was followed by a static footprint on a soft surface. On both occasions, the participants stood on an inkless mat and then on reactive paper, creating a two-dimensional print. The Reel method was used to analyse each footprint and the print was measured to see whether a difference existed between length and width (forefoot and rearfoot width) on a hard surface compared to a soft surface. The conclusion from this study was there is a statistically significant increase in length and width of a static bare footprint on a soft surface as opposed to a hard surface. If a forensic footprint examiner compares static bare footprints found on a soft surface and compares them to a static bare footprint of the same foot taken later, then the increase in both length and width of the footprints on a soft surface should be considered in the evaluation. Highlights: An increase in the mean length of a bare footprint on a soft surface An increase in the mean width (forefoot and heel) of a bare footprint on a soft surface Statistically significant increase in length of a bare footprint on a soft surface Statistically significant increase in width (forefoot and heel) of a bare footprint on a soft surface